Overwritten in Translation or a Translation Plagiarism of Grimms’ Tales - Pieciul-Karmińska, Eliza (Porównania, 2020)
The paper is a case study summarizing a recent translation plagiarism: a Polish translation of The Original Folk and Fairy Tales of the Brothers Grimm: the Complete First Edition by Jack Zipes (2014) presented by the publishing company WasPos as the first Polish translation of the German original Kinder- und Hausmärchen (1812/1815). The paper presents traces of the source American translation by Zipes in the Polish text, but also discusses additions introduced by the Polish publisher which were aimed at increasing the alleged brutality of the German fairy tale collection. Such a strategy reveals the Polish stereotype of Grimms’ Tales as cruel, gloomy and bloody. The presented story of a faked translation illustrates the main problems in the Polish reception of this world famous fairy tale collection.